The Influence of Social Support, Motivation, and Self-Regulation on Academic Achievement of Generation Z Students - Gracia Rachmi Adiarsi; Akhmad Edhy Aruman; Aditya Eka Putra; Latifa Ramonita; Sofia Meivina (Ikatan Sarjana Komunikasi Indonesia, 2026)
Social media has become an integral part of modern life, particularly for Generation Z as digital natives who actively engage with platforms such as Instagram, TikTok, and WhatsApp. While social media offers opportunities for interaction, information access, and self-expression, its impact on academic achievement remains paradoxical, as it can both support learning and create distractions. This study examines the influence of social support, motivation, and self-regulation on academic achievement, with social media usage patterns as mediating variable. Grounded in Uses and Gratifications Theory and Self-Determination Theory, this research employs a quantitative explanatory approach using PLS-SEM. Data were collected through a questionnaire from 300 undergraduate students at private universities in Jakarta. The findings indicate that social support, intrinsic and extrinsic motivation, and self-regulation significantly influence academic achievement, with self-regulation as the strongest predictor. Furthermore, the intensity and purpose of social media use significantly mediates these relationships, showing that academic outcomes depend on how students align social media use with learning goals. This study highlights that social media can function as a supportive academic tool when used purposefully. The novelty lies in integrating UGT and SDT with behavior constructs of self-regulation and social support to explain how mediated social media use shapes academic achievement among Generation Z students in Jakarta.